Learn Selenium : build data-driven test frameworks for mobile and web applications with Selenium Web Driver 3 - Gundecha, Unmesh; Cocchiaro, Carl (Packt Publishing, 2019)
Learn end-to-end automation testing techniques for web and mobile browsers using Selenium WebDriver, AppiumDriver, Java, and TestNG Key Features Explore the Selenium grid architecture and build your own grid for browser and mobile devices Use ExtentReports for processing results and SauceLabs for cloud-based test services Unlock the full potential of Selenium to test your web applications. Book Description Selenium WebDriver 3.x is an open source API for testing both browser and mobile applications. With the help of this book, you can build a solid foundation and can easily perform end-to-end testing on web and mobile browsers. You'll begin by being introduced to the Selenium Page Object Model for software development. You'll architect your own framework with a scalable driver class, Java utility classes, and support for third-party tools and plugins. You'll design and build a Selenium grid from scratch to enable the framework to scale and support different browsers, mobile devices, and platforms. You'll strategize and handle a rich web UI using the advanced WebDriver API and learn techniques to handle real-time challenges in WebDriver. You'll perform different types of testing, such as cross-browser testing, load testing, and mobile testing. Finally, you will also be introduced to data-driven testing, using TestNG to create your own automation framework. By the end of this Learning Path, you'll be able to design your own automation testing framework and perform data-driven testing with Selenium WebDriver. This Learning Path includes content from the following Packt products: Selenium WebDriver 3 Practical Guide - Second Edition by Unmesh Gundecha Selenium Framework Design in Data-Driven Testing by Carl Cocchiaro What you will learn Use different mobile and desktop browser platforms with Selenium 3 Use the Actions API for performing various keyboard and mouse actions Design the Selenium Driver Class for local, remote, and third-party grid support Build page object classes with the Selenium Page Object Model Develop data-driven test classes using the TestNG framework Encapsulate data using the JSON protocol Build a Selenium Grid for RemoteWebDriver testing Build and use utility classes in synchronization, file I/O, reporting and test listener classes Who this book is for This Learning Path is ideal for software quality assurance/testing professionals, software project managers, or software developers interested in using Selenium for testing their ...